ANALISIS PERFORMANCE COOLING TOWER TIPE INDUCED DRAFT COUNTER FLOW PLTP KAMOJANG UNIT 5 - Abdurohman, Hasan; Mrihardjono, Juli; Darmanto, Seno (universitas teuku umar, 2022)
Cooling tower is a heat exchanger used to cool water from the condenser. The process is carried out by contacting water with air directly and discharged into the atmosphere using air fluid that is flowed naturally or flowed by a fan. Cooling tower type used in PLTP Kamojang Unit 5 is Induced draft Counter Flow. This equipment more important in increasing turbine efficiency, therefore special treatment is needed by knowing and observing the performance of the Cooling tower so that it can be analyzed in actual conditions and make decision steps in carrying out further repairs and maintenance, this is the basis of research that will be carried out by looking for value and the Cooling tower performance trendline. The calculation method uses the standard ASME PTC 23-2003 and CTI ATC-105 where the results are the calculation baseline and the historical trendline of Cooling tower performance based on the parameters of the 3-cell Cooling tower operating conditions. The parameters tested are by taking 5 valid data on PLTP KMJ Unit 5, then the Tower Capability performance values are obtained as follows, namely in the initial commissioning conditions the performance value is 92,1%, Q1 2021 is 78,8%, Q3 2021 is 74, 3%, Q4 2021 is 84,7%, and Q1 2022 is 83,8%. There was a decrease in Q3 2021. Then there was an increase in the trend in Q4 2021 due to previous overhaul activities on the Cooling tower. Keywords: Cooling tower, trendline, overhaul, tower capability